2014
DOI: 10.1111/jcpp.12205
|View full text |Cite
|
Sign up to set email alerts
|

Variations in maternal 5‐HTTLPR affect observed sensitive parenting

Abstract: This study suggests that variations in maternal 5-HTTLPR genotype appear to be involved in the etiology of parenting behavior. The observed effects of this genetic variation are consistent with the notion that parenting may have a genetic component, but large studies are needed to find the specific small molecular effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 51 publications
3
49
1
Order By: Relevance
“…Mileva-Seitz et al speculated that the discrepant findings in those first two studies of the short 5HTT allele were owing to methodological differences: if it can be assumed that carriers of the short allele are more responsive to environments, both good and bad, then a less stressful experimental protocol (as in the Mileva-Seitz et al study involving home visits) might be associated with greater parental sensitivity than a more stressful experimental protocol (as in the BakermansKranenburg and Van IJzendoorn study involving structured laboratory tasks and children with high levels of externalizing behavior). The findings initially reported by were later replicated in a large cohort using repeated measures of observed maternal sensitivity (Cents et al, 2014). A twin study revealed a gender effect in the association between the short allele and parenting: for mothers of boys, positive parenting decreased with the number of maternal short alleles, whereas for mothers of girls positive parenting was not associated with the number of short alleles (Pener-Tessler et al, 2013).…”
Section: Serotonin and Human Motheringmentioning
confidence: 81%
“…Mileva-Seitz et al speculated that the discrepant findings in those first two studies of the short 5HTT allele were owing to methodological differences: if it can be assumed that carriers of the short allele are more responsive to environments, both good and bad, then a less stressful experimental protocol (as in the Mileva-Seitz et al study involving home visits) might be associated with greater parental sensitivity than a more stressful experimental protocol (as in the BakermansKranenburg and Van IJzendoorn study involving structured laboratory tasks and children with high levels of externalizing behavior). The findings initially reported by were later replicated in a large cohort using repeated measures of observed maternal sensitivity (Cents et al, 2014). A twin study revealed a gender effect in the association between the short allele and parenting: for mothers of boys, positive parenting decreased with the number of maternal short alleles, whereas for mothers of girls positive parenting was not associated with the number of short alleles (Pener-Tessler et al, 2013).…”
Section: Serotonin and Human Motheringmentioning
confidence: 81%
“…Nobile et al, 2008;Campbell et al, 2013;Chen, Li, & McGue, 2013;Cents et al, 2014). Some considerations on which JCPP's decisions whether to accept or reject reports of trait/disorder-gene association may guide authors when planning their studies; however, under certain circumstances other types of studies might add value and may be acceptable too.…”
mentioning
confidence: 99%
“…Specifically, the s-allele is associated with more sensitive parenting [60]. Two further studies have investigated the relationship between this polymorphism and PPD.…”
Section: Genetic Factors Potentially Involved In Reward Deficiency Inmentioning
confidence: 99%
“…This was most evident in mothers delivering during autumn/winter. A further interaction of this polymorphism was found with the 5-HTTLPR s-allele [71], which is involved in maternal sensitivity [60]. Another study in 227 subjects found no difference in BDNF genotype between depressed and non-depressed women [72].…”
Section: Genetic Factors Potentially Involved In Reward Deficiency Inmentioning
confidence: 99%